1985
DOI: 10.1104/pp.77.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peroxisomes from the Alga Bumilleriopsis filiformis

Abstract: The Xa"thophycean alp Bumilkropsis filiformis possesses peroxisomes which on electron micrographs show a mostly spherical or ovoid shape with a diameter in the range of 03 micrometer. Their Microbodies have been demonstrated by electron microscopy to be present in many different algae (18), but only from a few of those organisms could the microbodies be isolated for biochemical characterization. Nevertheless, it has already become evident that there are different types ofalgal microbodies (7, 23).In Spirogyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the Xanthophyte Bumilleriopsis another variation of this pathway was observed. This alga possesses a glycolate oxidase, but the second key enzyme, hydroxypyruvate reductase, is absent ( 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Xanthophyte Bumilleriopsis another variation of this pathway was observed. This alga possesses a glycolate oxidase, but the second key enzyme, hydroxypyruvate reductase, is absent ( 13).…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly true for the Chlorophytes, Bacillariophytes, and Euglenophytes (12), but recent studies have shown that in Charophytes (27), Xanthophytes (13), and Cyanophora (3) a glycolate oxidase is present. The finding that the enigmatic alga Cyanidium also possesses a glycolate oxidase suggests that among the algae a glycolate oxidase is more widespread than previously assumed.…”
Section: Determination Of Native Mol Wtmentioning
confidence: 99%
“…In the chlorophyte Eremosphaera viridis (33) and in four Prasinophycean algae (29), a dual localization has been found similar to the situation in mammalian tissue. A solely mitochondrial location is present in the xanthophyte Bumilleriopsisfiliformis (14). (The results reported by Graves and Becker [12] on the distribution of f-oxidation enzymes in heterotrophically grown Euglena are not conclusive.)…”
mentioning
confidence: 67%
“…Although only a few algae have been examined, it is already clear that, in contrast to the consistent picture observed within mammalian and higher plant groups respectively, several dispositions of the enzymes of 1-oxidation occur within this single group. An exclusively peroxisomal location has been found in the charophyte Mougeotia (28), a dual site of 1-oxidation in the chlorophyte Eremosphaera (33) as well as in several Prasinophytes (29) and a mitochondrial location in the xanthophyte Bumilleriopsis (14) and in Cyanidium. Such differences may have taxonomic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation